Politeness and Respect in Indonesian Traditions: An Ethnographic Communication Perspective - Jumriani, Jumriani; Putri, Andi Dian Fitriana Eka; Muhtar, Muhtar; Ophir, Yotam (Feedback International Journal of Communication, 2024)
This study explores the Mahpangngolo tradition, a ceremonial procession integral to celebrations among the people of Enrekang, Indonesia. The tradition symbolizes community participation and reinforces values of politeness and respect. However, younger generations are increasingly disengaged from such cultural practices, threatening their preservation. An ethnographic communication approach was employed, involving observations, interviews, and documentation. Dell Hymes' SPEAKING model (Situation, Participants, Ends, Act Sequence, Key, Instrumentalities, Norms, Genres) served as the analytical framework for understanding the communicative dimensions of Mahpangngolo. The Mahpangngolo procession emphasizes the symbolic exchange of gifts between guests and hosts. This act is marked by the use of formal and polite language, reflecting mutual respect and community cohesion. Specific expressions by guest representatives and celebration family members underscore the cultural significance of respect and politeness. The findings highlight the Mahpangngolo tradition as a medium for transmitting core values of Indonesian society. Addressing the indifference of younger generations requires initiatives to promote cultural understanding and appreciation. The Mahpangngolo tradition embodies politeness and respect, core values that strengthen communal bonds. Efforts to preserve and promote these traditions are vital for maintaining cultural heritage.